Pathway analysis and optimization in metabolic engineering - Torres, Néstor V., 1958- (Cambridge University Press, 2002)
This book introduces methods of optimizing biochemical systems of biotechnological relevance. It examines the development of strategies for manipulating metabolic pathways and discusses the design and analysis of systems models. All concepts are derived from first principles, the text is illustrated with graphs and examples, and two detailed case studies are presented.